Depersonalization–derealization disorder: a contemporary review of definitions, neurobiology, and treatment approaches. - Czechowicz, Marta; Madoń, Joanna; Gadziński, Patryk (Journal of Education, Health and Sport, 2025)
Background Depersonalization/derealization disorder (DPDR) is a rare mental disorder in which patients experience a sense of detachment from themselves or their surroundings. Despite clearly defined diagnostic criteria, this disorder is often unrecognized or confused with other mental illnesses, such as depression or anxiety disorders. Aim This article aims to review the current knowledge on the definition, epidemiology, clinical knowledge, neurobiology, and treatment options for DPDR. Materials and Methods A narrative review of the literature available in PubMed, Google Scholar, and Web of Science databases was conducted. The analysis covered works published up to December 2025. Results DPDR affects approximately 1% of the general population and often co-occurs with other mental disorders. Symptoms may be episodic or chronic and significantly affect patients' quality of life. Cognitive-behavioral therapy remains the best-documented treatment, while the effectiveness of pharmacotherapy and neuromodulation remains unclear due to limited studies. Conclusions DPDR is a distinct and clinically significant disorder that warrants greater diagnostic and therapeutic attention. Further research, extensive controlled clinical trials, is needed to develop more effective treatment strategies.